2010
DOI: 10.1016/j.archoralbio.2010.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Full length amelogenin binds to cell surface LAMP-1 on tooth root/periodontium associated cells

Abstract: Objectives-Lysosome-associated membrane protein-1 (LAMP-1) has been suggested to be a cell surface receptor for a specific amelogenin isoform, leucine-rich amelogenin peptide or LRAP. However, it is unclear if LAMP-1 is an amelogenin receptor for dental mesenchymal cells. The goal of this study was to determine if LAMP-1 serves as a cell surface binding site for full length amelogenin on tooth root/periodontium associated mesenchymal cells.Design-Murine dental follicle cells and cementoblasts (OCCM-30) were cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 64 publications
2
41
0
Order By: Relevance
“…Previous studies have reported that recombinant full-length amelogenin (rh174 or rm180) binds to LAMP-1 or LAMP-3 expressed on the cell membrane of cementoblasts 21,25) , and that the presence of LAMP-3 antibody in the culture medium inhibited the cementoblast proliferation promoted by rh174 25) . Furthermore in cementoblast, LRAP showed no effect on cell proliferation 36) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that recombinant full-length amelogenin (rh174 or rm180) binds to LAMP-1 or LAMP-3 expressed on the cell membrane of cementoblasts 21,25) , and that the presence of LAMP-3 antibody in the culture medium inhibited the cementoblast proliferation promoted by rh174 25) . Furthermore in cementoblast, LRAP showed no effect on cell proliferation 36) .…”
Section: Discussionmentioning
confidence: 99%
“…LAMPs are not only present in the lysosome membrane but are also present in endosomes, phagosomes, and cell surfaces 17) . Since LAMP-1 and LAMP-3 are identified as binding partners for mouse amelogenin 18,19) , several studies have reported that LAMP-1 expressed on the cell membrane binds to amelogenin and could be a signaling receptor for amelogenin 20,21) . However, the detailed mechanism by which th e amelogenin isoform ind uces chondrogenesis or osteogenesis is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that LAMP-1 can serve as a cell surface-binding site for not only for LRAP but also full-length amelogenin on cementoblasts (Zhang et al, 2010). Furthermore LAMP-1 expressed in bone marrow mesenchymal stem cells and full-length amelogenin signaling through LAMP-1 would be involved in mesenchymal cell proliferation through the MAPK-ERK pathway (Huang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…By using the yeast 2-hybrid (Y2H) system it has been identified that LAMP-1 and LAMP-3 are binding partners for mouse amelogenin (Zou et al, 2007). A recent study showed that LAMP-1 can serve as a cell surface binding site for amelogenin on cementoblasts (Zhang et al, 2010). However, the distribution of amelogenin and LAMPs in cartilage and its development is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…can serve as a cell surface binding site for amelogenin on cementoblasts 14) . However the distribution of these LAMPs in …”
Section: Introductionmentioning
confidence: 99%